2017
DOI: 10.1149/07532.0013ecst
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching Comparison between Cu/TaOx/Ru and Cu/TaOx/Pt Memory Cells

Abstract: Building nonvolatile memory (NVM) directly into a CMOS lowk/Cu interconnect module would reduce latency in connectivity constrained devices and reduce chip's footprint by stacking memory on top of the logic circuits. One good candidate for NVM is the wellbehaved Cu/TaO x /Pt resistive switching device. However, since platinum (Pt) is not an economic choice for industrial production, a BEOL-compatible replacement of Pt is highly desirable. A good candidate to replace Pt is ruthenium (Ru) which has been already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…[27]. However, in our previous study [28], we have found the Ru device far inferior to the Pt device. The degradation of the electrical behavior has been attributed to the loss of Cu atoms from the conductive filament either due to Cu surface diffusion at the Ru/TaO x interface or due to a diffusion of Cu into Ru electrode layer.…”
Section: Introductionmentioning
confidence: 67%
“…[27]. However, in our previous study [28], we have found the Ru device far inferior to the Pt device. The degradation of the electrical behavior has been attributed to the loss of Cu atoms from the conductive filament either due to Cu surface diffusion at the Ru/TaO x interface or due to a diffusion of Cu into Ru electrode layer.…”
Section: Introductionmentioning
confidence: 67%
“…In evaluating Equation (), one has to take into account the temperature dependence of the specific heat capacity which – for an exact solution – would require numerical solution. [ 37 ] The heat capacity of metals varies with temperature according to the Debye theory and displays strong dependence with up to slightly below the Debye temperature, T D , of the material. [ 36 ] Around and above T D , the specific heat capacity of metals increase only modestly with increasing temperature.…”
Section: Thermal Analysis Predictions Of Reram Cells’ Degradation And...mentioning
confidence: 99%
“…Assuming a truncated cone shape of nanofilament with a radius of 8 nm at the bottom, and 5 nm top radius, and 25 nm height, given by the thickness of the TaO x , the volume comes to 4.6 × 10 ‐18 cm 3 . [ 37 ] This volume and geometry lead to a R on resistance of ≈1000 Ω, if one assumes the resistivity of the Cu NF of 5 × 10 −4 Ωcm, ≈20 times higher than that the resistivity of bulk Cu. Indeed, such R on value is observed experimentally at I cc = 10 µA.…”
Section: Thermal Analysis Predictions Of Reram Cells’ Degradation And...mentioning
confidence: 99%
“…In [34,35] the electric performances of Cu/TaO x /Ru and Cu/TaO x /Pt devices have been compared. It was found that the performance of the Ru device is far inferior to that of the Pt device.…”
Section: The Device Embedment Issuementioning
confidence: 99%
“…In [34] it was found that the Ru device(a) can be switched a limited number of times at a high compliance current I cc (~ 0. Because of the chemical reactions triggered by the local high temperatures caused by RS switching behavior, the Ru devices show different properties over the stable Pt devices.…”
Section: The Device Embedment Issuementioning
confidence: 99%